"Beyond Spain: Inquisition History in a Global Context". Issue 4 (19th March 2013) - Vose, Robin
Abstract Recent developments in Italian, Portuguese and colonial inquisition histories around the globe have greatly enhanced our knowledge both of these persecuting bodies' own institutional nature and of the varied sorts of human experience they sought to discipline. Social historians continue to find evidence for a wide range of premodern mentalities and lifeways in inquisitorial and related trial documents, not only in Europe but among indigenous and subaltern peoples in colonial settings as well. At the same time, studies of inquisitorial personnel, policies and organizational structures are contributing to broader historiographies of religion and politics in the late medieval and early modern periods. The future of inquisition history now requires increased collaboration and sharing of research across traditional divides of region, confession, and specialization.